An anti-oxygen / antistatic organosilane / reduced graphene oxide composite surface modified film and preparation method thereof

Through the chemical bonding reaction between organosilane and reduced graphene oxide composite system, the anti-atomic oxygen and anti-static properties on the surface of the polymer matrix are improved, and the problems of poor brittleness and matching of the coating in the prior art are solved, and efficient anti-atomic oxygen and anti-static effects are achieved.

CN116239809BActive Publication Date: 2025-04-08SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111493332.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-08
Publication Date
2025-04-08
Estimated Expiration
2041-12-08

AI Technical Summary

Technical Problem

In the prior art, when anti-atomic oxygen/antistatic functionalized modified polymer materials, it is difficult to form a continuous and dense atomic oxygen inert structure, and the coating is brittle and poorly matched with the substrate, which easily leads to defects such as shedding and cracks.

Method used

The composite system of organosilane and reduced graphene oxide is adopted to improve the bonding of graphene oxide and polymer matrix through chemical bonding reaction, forming an anti-atomic oxygen/anti-static composite surface modified film.

Benefits of technology

A gradient gradient layer with a depth of about 1 μm on the surface of the polymer matrix is ​​realized, which improves anti-atomic oxygen performance and anti-static properties, reduces mass loss and surface resistance, and complies with NASA's spatial anti-static standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116239809B_ABST
    Figure CN116239809B_ABST
Patent Text Reader

Abstract

The present invention relates to an anti-proton oxygen / antistatic organosilane / reduced graphene oxide composite surface modified film and a preparation method thereof. The anti-proton oxygen / antistatic organosilane / reduced graphene oxide composite surface modified film comprises: a polymer matrix, and a mixed layer of organosilane and reduced graphene oxide formed on the surface of the polymer matrix; wherein the organosilane simultaneously undergoes bonding reaction with the polymer matrix and the reduced graphene oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an anti-oxygen / antistatic organosilane / reduced graphene oxide composite surface modified film and a preparation method thereof, belonging to the technical field of surface modification. Background Art

[0002] Polymer materials are flexible, lightweight, low-cost, and easy to process. They are important components of household appliances, electronic information, automotive industry, aerospace, and other fields. As an important material closely related to the national economy, high-tech technology, and modern life, they have played a huge role in various fields. For example, polyimide (PI) has outstanding comprehensive performance. Its high and low temperature stability, high strength, good flexibility, light weight, radiation resistance, and low outgassing rate make it an irreplaceable polymer material in the aerospace field and widely used in thermal control, power supply, and structural systems. PI used on the surface of low-orbit spacecraft thermal control coatings is directly exposed to atomic oxygen, plasma, ultraviolet, and hot and cold alternation environments in space. Among them, atomic oxygen is the most dangerous environmental factor for PI surface damage and degradation. Plasma charging and discharging can cause failures in some components of the spacecraft, and anti-oxygen / antistatic functional modification is required.

[0003] For the functional modification of PI to resist proton oxygen / antistatic, the overall change of the composition structure of PI has a great influence on the original mechanical properties of the PI matrix, and it is difficult to form a continuous and dense atomic oxygen inert structure. According to the mechanism of action between atomic oxygen and materials, if a dense atomic oxygen inert layer with adhesion can be formed on the surface of PI, it can prevent the erosion of the inner matrix by atomic oxygen. An effective method for antistatic is to make the surface have a certain conductivity and be connected to the planet. The use of surface protective coating can combine the excellent performance of the polymer matrix (such as PI) with the protective performance of the coating itself, which is a commonly used protection method at home and abroad. Among them, the vacuum deposited indium tin oxide (ITO) coating on the surface of PI has been widely used in the field of thermal control coatings. ITO itself has the dual functions of resist proton oxygen / antistatic. However, during the use of processing, storage and transportation and the synergistic effect of multiple factors in complex space environments, it is easy to produce defects such as shedding and cracks due to the brittleness of the coating itself and poor adhesion and matching with the substrate, resulting in atomic oxygen accelerating the erosion of the matrix PI from the defects and the decline of electrical performance, causing equipment failure.

[0004] Therefore, in view of the application requirements of anti-proton oxygen / anti-static, a modification system suitable for PI surface is developed to solve the problem of shedding and cracking during use, and to realize the dual functions of anti-proton oxygen / anti-static, which has important application value. Summary of the invention

[0005] In view of the application requirements of anti-proton oxygen / anti-static, especially the application requirements in complex space environments, the present invention aims to provide a method for anti-proton oxygen / anti-static composite surface modification using organic silane / reduced graphene oxide.

[0006] On the one hand, the present invention provides an anti-oxygen / antistatic organosilane / reduced graphene oxide composite surface modified film, comprising: a polymer matrix, and a mixed layer of organosilane and reduced graphene oxide formed on the surface of the polymer matrix; wherein the organosilane simultaneously undergoes a bonding reaction with the polymer matrix and the reduced graphene oxide.

[0007] In the present invention, a method for anti-proto-oxygen / antistatic modification using an organosilane / reduced graphene oxide composite system is provided. The method utilizes the chemical reaction bonding of organosilane with a polymer matrix and graphene oxide to improve the binding property of graphene oxide with a polymer matrix. The system combines the excellent anti-proto-oxygen performance of the Si system with the conductivity, flexibility, and high barrier properties of reduced graphene oxide. An organosilane / reduced graphene oxide composite system is prepared, and the polymer matrix is ​​surface treated using the composite system to obtain an anti-proto-oxygen / antistatic surface that is excellent in bonding with the polymer matrix. Preferably, polyimide film and polyester film. Wherein, carboxyl groups exist on the surface of the modified polyimide film, and the organosilane reacts with the polymer matrix to form Si-OC bonds, etc. Carboxyl groups exist on the surface of the modified polyester film, and the organosilane reacts with the polymer matrix to form Si-OC bonds, etc. At the same time, the reaction between the organosilane and the reduced graphene oxide forms -Si-OC- bonds and peptide bonds.

[0008] Preferably, the organosilane is an aminohydrocarbon silane, selected from at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, aminopropylmethyldiethoxysilane and N-aminoethyl-3-aminopropyltriethoxysilane.

[0009] Preferably, the mass ratio of the reduced graphene oxide to the organosilane is 1:(1-5).

[0010] Preferably, the thickness of the mixed layer of organosilane and reduced graphene oxide is 50 nm to 10 μm.

[0011] Preferably, the polymer matrix is ​​a polyimide film, a polyester film or a composite film of the two.

[0012] On the other hand, the present invention provides a method for preparing an anti-oxygen / antistatic organosilane / reduced graphene oxide composite surface modified film, comprising:

[0013] hydrolyzing the organosilane to obtain a hydrolyzed functional organosilane;

[0014] mixing the graphene oxide solution and the hydrolyzed functional organosilane to obtain a mixed solution;

[0015] The mixed solution is spin-coated on the surface of the polymer substrate, and heat-treated at 100-200° C. for 1-48 hours to obtain an anti-proton oxygen / antistatic organic silane / reduced graphene oxide composite surface modified film.

[0016] In the present disclosure, the dispersed graphene oxide alcohol solution is added dropwise to the hydrolyzed 3-aminopropyltriethoxysilane organosilane solution and stirred at a certain temperature. Since the hydrolyzed 3-aminopropyltriethoxysilane and the graphene oxide prepared by the Hummers method both contain abundant functional groups that can react with each other, the two can be bonded by stirring and mixing. Subsequently, the mixed solution is coated on the surface of the activated pretreated PI substrate by spin coating to obtain an organosilane / graphene oxide composite modified film layer, and then heat-treated at a certain temperature, the purpose is to make the functional groups in the organosilane / graphene oxide mixed solution fully react and bond with the activated PI substrate surface functional groups, and to reduce the graphene oxide to reduced graphene oxide to increase the surface conductivity. Specifically, by adjusting the mass ratio of organosilane and graphene oxide in the mixed solution, a composite surface modified film layer with different conductivity and different AO protection effect can be formed. The above 3-aminopropyltriethoxysilane is only used as an example, and other silanes such as 3-aminopropyltrimethoxysilane, aminopropylmethyldiethoxysilane, N-aminoethyl-3-aminopropyltriethoxysilane, etc. are also prepared using the above method. Graphene oxide is prepared using the Hummers method, and graphene oxide powder is freeze-dried to obtain alcohol, which is then ultrasonically dispersed to obtain a graphene oxide alcohol solution.

[0017] Preferably, the mass ratio of the graphene oxide to the organosilane is 1:(1-5), preferably 1:(2-4).

[0018] Preferably, the polymer matrix is ​​subjected to acid-base activation treatment before spin coating; the solution used for the acid-base activation treatment includes a NaOH solution with a concentration of 0.5-5 mol / mL and an acetic acid solution with a concentration of 0.5-5 mol / mL. After the polyimide film is subjected to alkali activation treatment, an imide ring opening reaction occurs on the surface, and a large number of carboxylic acid groups are generated after the acid activation reaction. The polyester film has ester groups, and after the acid-base activation treatment, a saponification reaction occurs and hydrolyzes into terephthalic acid.

[0019] Preferably, the coating method is spin coating or spray coating; the spin coating speed is 500 to 3000 rpm, and the spin coating time is 1 to 60 seconds.

[0020] Beneficial effects:

[0021] The organosilane / reduced graphene oxide composite modification system used in the present invention can react chemically with the polymer matrix and graphene oxide to effectively improve the bonding between graphene oxide and the polymer matrix. The prepared organosilane / reduced graphene oxide modified film layer has excellent bonding performance with PI, and a gradient layer with a depth of about 1 μm is formed on the PI surface. After 100 simulated space cold and hot cycles at -100°C to 100°C, there is no cracking or shedding on the surface. The modified PI can be made at 8.01×10 20 atoms / cm 2 Under the cumulative AO bombardment, the mass loss is reduced by 78% to 99% compared with the original PI; the surface resistance is reduced by 6 to 10 orders of magnitude compared with the original PI, which meets the space anti-static 10 set by NASA. 6 ~10 10 Ω / □ Surface electrical performance standard. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the bonding and functional group Fourier infrared characterization spectrum after the reaction of organosilicon and graphene oxide in the process of preparing the organosilicon / reduced graphene oxide modified film layer in Example 3 (wherein the ordinate is absorbance and the abscissa is wavenumber). It can be seen from the figure that the silanol of organosilicon reacts with the carboxyl group of graphene oxide to form a Si-OC bond, and the amino group of organosilicon reacts with the carboxyl group of graphene oxide to form a peptide bond, indicating that the organosilicon and graphene oxide have undergone a sufficient bonding reaction;

[0023] Figure 2 This is the Fourier infrared characterization spectrum of the bonding and functional groups of the acid-base modified polyimide during the preparation of the organosilicon / reduced graphene oxide modified film in Example 3 (where the ordinate is absorbance and the abscissa is wavenumber). It can be seen from the figure that the characteristic peak of the imide ring disappears after the bond modification of the original polyimide film, indicating that the imide ring is opened and a carboxyl group is generated to form polyamic acid after acid treatment;

[0024] Figure 3 This is the Fourier transform infrared characterization spectrum of the surface functional groups of the organosilicon / reduced graphene oxide modified film layer prepared in Example 3 (wherein the ordinate is absorbance and the abscissa is wavenumber). It can be seen from the figure that the silanol groups in the organosilicon / reduced graphene oxide modified system react with the carboxyl groups on the surface of the polyimide after acid-base modification to generate Si-OC bonds, indicating that a bonding reaction occurs between the modified film layer and the polyimide matrix;

[0025] Figure 4The Fourier transform infrared characterization spectrum of the surface functional groups of the organosilicon-modified film layer prepared in Comparative Example 2 compared with the original polyimide functional groups (where the ordinate is absorbance and the abscissa is wavenumber). It can be seen from the figure that the silanol groups of the organosilicon react with the carboxyl groups on the surface of the acid-base modified polyimide to generate Si-OC bonds, indicating that the organosilicon can undergo bonding reactions with the acid-base modified polyimide;

[0026] Figure 5 This is a surface SEM image of the organosilicon / reduced graphene oxide modified film layer prepared in Example 3. From the image, it can be seen that the surface of the organosilicon / reduced graphene oxide modified film layer has graphene flakes and organosilicon covering the surface;

[0027] Figure 6 This is a surface SEM image of the organosilicon / reduced graphene oxide modified film layer prepared in Example 3 after 100 times of -100 to 100°C simulated space thermal cycling. It can be seen from the figure that after the thermal cycling simulation, the organosilicon / reduced graphene oxide modified film layer has no obvious signs of damage, indicating that the organosilicon / reduced graphene oxide modified film layer can effectively resist the space thermal cycling service conditions;

[0028] Figure 7 The cross-sectional SEM image (upper part) and cross-sectional EDS line scanning Si Kα1 spectrum (lower part; where the ordinate is the absorption intensity (au) and the abscissa is the thickness (μm)) of the organosilicon / reduced graphene oxide modified film layer prepared in Example 5. It can be seen from the figure that the organosilicon modification depth is greater than the modified film layer thickness, and a modified gradient layer is generated on the surface of the polyimide substrate;

[0029] Figure 8 This is an optical microscope characterization image of the organosilicon / reduced graphene oxide modified film layer prepared in Example 3 before and after the 3M adhesive bonding test. It can be seen from the figure that there is no sign of the film layer falling off after the organosilicon / reduced graphene oxide modified film layer is bonded with 3M adhesive, indicating that the modified film layer has good bonding with the substrate;

[0030] Fig. 9 This is an optical microscope characterization image of the pure reduced graphene oxide modified film layer prepared in Comparative Example 1 before and after the 3M adhesive bonding test. It can be seen from the figure that the pure reduced graphene oxide modified film layer without silicone modification has obvious signs of film shedding after 3M adhesive bonding, indicating that the pure reduced graphene oxide modified film layer has poor bonding with the polyimide matrix;

[0031] Fig.10This is a surface SEM image of the organosilicon modified film layer prepared in Comparative Example 2. It can be seen from the figure that the pure organosilicon modified film layer without graphene will crack when the preparation environment and other conditions are not well controlled. DETAILED DESCRIPTION

[0032] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0033] In the present disclosure, the hydrolyzed 3-aminopropyltriethoxysilane organosilane solution is mixed with graphene oxide prepared by the Hummers method, and then coated on the PI surface by spin coating, and then heat treated at a certain temperature to form an organosilane / reduced graphene oxide coating with anti-atomic oxygen / anti-static function.

[0034] Taking 3-aminopropyltriethoxysilane as an example, the preparation method of the organosilane / reduced graphene oxide coating is exemplarily described below.

[0035] Preparation of organic silane / reduced graphene oxide mixed solution. Add a small amount of deionized water to 3-aminopropyltriethoxysilane and stir at room temperature for 1 to 48 hours (e.g., 12 hours) for hydrolysis. Disperse graphene oxide powder in an alcohol solution, and after low-temperature ultrasonic dispersion for 1 to 24 hours (e.g., 6 hours), slowly drop the dispersed graphene oxide alcohol dispersion into the hydrolyzed 3-aminopropyltriethoxysilane solution, stir at 15 to 60° C. (e.g., 35° C.) for 1 to 24 hours (e.g., 12 hours) to complete the preparation. In the present disclosure, the selected graphene oxide concentration may be 1 to 5 mg / mL, such as 3 mg / mL, 4 mg / mL and 5 mg / mL. The mass ratio of graphene oxide to 3-aminopropyltriethoxysilane selected is 1: (1 to 5), such as 1: 2, 1: 3 and 1: 4.

[0036] Preparation of PI surface organic silane / reduced graphene oxide surface modified film layer. First, the PI substrate is acid-base modified and dried under vacuum and room temperature conditions. The modified PI is cut into a certain size and fixed on a spin coater, and the rotation speed is adjusted to 500-3000rpm (for example, 1000rpm). 3-aminopropyltriethoxysilane / graphene oxide solution of different ratios is dripped on PI, and the spin coating is completed after 1-60 seconds (for example, 15s). Then take it out and put it in a 50-150℃ (for example, 80℃) oven for drying for 1-120 seconds (for example, 30s). Then repeat the above spin coating and drying steps 1-20 times (for example, 6 times), and the spin coating is completed. After the spin coating is completed, the sample is placed in an oven and heated at 100℃, 150℃ and 200℃ for 4h for heat treatment to obtain a 3-aminopropyltriethoxysilane / reduced graphene oxide surface modified film layer. Among them, in addition to spin coating, spray coating and coating are also possible.

[0037] The advantages of the method described in the present invention are: the graphene oxide prepared by the small molecule organic silane reagent 3-aminopropyltriethoxysilane and the Hummers method has abundant organic groups and can form a strong bond with the surface of the PI after surface activation. This surface modification method prepares a coating on the surface of PI, which has a strong bond with the PI substrate and has good flexibility like the PI substrate, and is suitable for low-orbit space application environment. In addition, only a simple heat treatment step is required to form a silicon oxide layer after heat treatment of 3-aminopropyltriethoxysilane, which can effectively protect PI from oxidative erosion by AO in low-orbit space; at the same time, the graphene oxide can be reduced, effectively modifying the electrical properties of the PI surface, and giving the PI surface better antistatic properties.

[0038] Test: A ground-based atomic oxygen simulation test device was used to simulate the corrosion of samples by low-orbit atomic oxygen. A precision balance was used to weigh the mass change. Raman spectroscopy was used to detect graphene oxide and the reduction effect of heat treatment. X-ray photoelectron spectroscopy was used to detect the bonding state of the sample surface. A scanning electron microscope was used to observe the surface morphology of the sample. X-ray energy spectrum was used to analyze the Si element reaction depth of the sample cross section.

[0039] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0040] Example 1

[0041] Under the 3mg / mL reduced graphene oxide concentration system, a composite modified system with a mass ratio of reduced graphene oxide to organic silane of 1:3 was prepared. 4.5mg of deionized water was added to an alcohol solution (3mL) containing 45mg of 3-aminopropyltriethoxysilane, and stirred at 360rpm for 12 hours at 25°C for hydrolysis. 15mg of graphene oxide powder prepared by the Hummers method was added to 2mL of alcohol solution, ultrasonically dispersed in an ice bath for 6 hours, and then the graphene oxide solution was slowly added dropwise to the hydrolyzed 3-aminopropyltriethoxysilane alcohol solution, and stirred at 180rpm for 12 hours at 25°C.

[0042] Preparation and characterization of PI surface composite modified film layer. The surface activated PI substrate was cut into 2.5×3 cm rectangles, fixed on a spin coater, and the rotation speed was adjusted to 1000 rpm. Different ratios of 3-aminopropyltriethoxysilane / graphene oxide solution were dripped on the PI surface, and immediately removed after spin coating for 15 seconds and placed in an 80°C oven for drying for 30 seconds. The above steps were repeated 6 times to complete the spin coating. After the spin coating was completed, the sample was placed in an oven and heated at 100°C, 150°C and 200°C for 4 hours for heat treatment to obtain a 3-aminopropyltriethoxysilane / reduced graphene oxide composite surface modified film layer.

[0043] The surface resistance of the 3-aminopropyltriethoxysilane / reduced graphene oxide coating under this mass ratio is 8.98×10 8 Ω / □After the cumulative dose is 8.01×10 20 atoms / cm 2 The mass loss after the ground atomic oxygen simulation test decreased by 88.0% compared with the original PI.

[0044] Example 2

[0045] Under the 4mg / mL reduced graphene oxide concentration system, a composite modified system with a mass ratio of reduced graphene oxide to organic silane of 1:2 was prepared. 4mg of deionized water was added to 2mL of alcohol solution containing 40mg of 3-aminopropyltriethoxysilane, and the mixture was stirred at 360rpm for 12 hours at 25°C for hydrolysis. 20mg of graphene oxide powder prepared by the Hummers method was added to 3mL of alcohol solution, ultrasonically dispersed in an ice bath for 6 hours, and then the graphene oxide solution was slowly added dropwise to the hydrolyzed 3-aminopropyltriethoxysilane alcohol solution, and stirred at 180rpm for 12 hours at 25°C.

[0046] Preparation and characterization of PI surface composite modified film layer. The surface activated PI substrate was cut into 2.5×3 cm rectangles, fixed on a spin coater, and the rotation speed was adjusted to 1000 rpm. Different ratios of 3-aminopropyltriethoxysilane / graphene oxide solution were dripped on the PI surface, and immediately removed after spin coating for 15 seconds and placed in an 80°C oven for drying for 30 seconds. The above steps were repeated 6 times to complete the spin coating. After the spin coating was completed, the sample was placed in an oven and heated at 100°C, 150°C and 200°C for 4 hours for heat treatment to obtain a 3-aminopropyltriethoxysilane / reduced graphene oxide composite surface modified film layer.

[0047] The surface resistance of the 3-aminopropyltriethoxysilane / reduced graphene oxide coating under this mass ratio is 1.28×10 6 Ω / □After the cumulative dose is 8.01×10 20 atoms / cm 2 The mass loss after the ground atomic oxygen simulation test decreased by 93.7% compared with the original PI. After 100 hot and cold cycles at -100 to 100°C, the surface SEM morphology did not change significantly.

[0048] Example 3

[0049] Under the 4mg / mL reduced graphene oxide concentration system, a composite modified system with a mass ratio of reduced graphene oxide to organic silane of 1:3 was prepared. 6mg of deionized water was added to 2mL of alcohol solution containing 60mg of 3-aminopropyltriethoxysilane, and the mixture was stirred at 360rpm for 12 hours at 25°C for hydrolysis. 20mg of graphene oxide powder prepared by the Hummers method was added to 3mL of alcohol solution, and ultrasonically dispersed in an ice bath for 6 hours. After that, the graphene oxide solution was slowly added dropwise to the hydrolyzed 3-aminopropyltriethoxysilane alcohol solution, and stirred at 180rpm for 12 hours at 25°C.

[0050] Preparation and characterization of PI surface composite modified film layer. The surface activated PI substrate was cut into 2.5×3 cm rectangles, fixed on a spin coater, and the rotation speed was adjusted to 1000 rpm. Different ratios of 3-aminopropyltriethoxysilane / graphene oxide solution were dripped on the PI surface, and immediately removed after spin coating for 15 seconds and placed in an 80°C oven for drying for 30 seconds. The above steps were repeated 6 times to complete the spin coating. After the spin coating was completed, the sample was placed in an oven and heated at 100°C, 150°C and 200°C for 4 hours for heat treatment to obtain a 3-aminopropyltriethoxysilane / reduced graphene oxide composite surface modified film layer.

[0051] The surface resistance of the 3-aminopropyltriethoxysilane / reduced graphene oxide coating under this mass ratio is 2.93×10 7Ω / □After the cumulative dose is 8.01×10 20 atoms / cm 2 The mass loss after the ground atomic oxygen simulation test was reduced by 97.0% compared with the original PI. After 100 cold and hot cycles at -100 to 100 °C, the surface SEM morphology did not change significantly. The cross-sectional SEM image shows that the coating thickness is about 900nm, and the cross-sectional EDS shows that the Si element reaction depth is at least 1.6μm. After AO bombardment, there is SiO on the surface. x form.

[0052] Example 4

[0053] Under the 4mg / mL reduced graphene oxide concentration system, a composite modified system with a mass ratio of reduced graphene oxide to organic silane of 1:4 was prepared. 8mg of deionized water was added to 2mL of alcohol solution containing 80mg of 3-aminopropyltriethoxysilane, and the mixture was stirred at 360rpm for 12 hours at 25°C for hydrolysis. 20mg of graphene oxide powder prepared by the Hummers method was added to 3mL of alcohol solution, ultrasonically dispersed in an ice bath for 6 hours, and then the graphene oxide solution was slowly added dropwise to the hydrolyzed 3-aminopropyltriethoxysilane alcohol solution, and stirred at 180rpm for 12 hours at 25°C.

[0054] Preparation and characterization of PI surface composite modified film layer. The surface activated PI substrate was cut into 2.5×3 cm rectangles and glued to the surface of the glass slide with transparent glue. The glass slide was then adsorbed on the spin coater and the rotation speed was adjusted to 1000 rpm. Different ratios of 3-aminopropyltriethoxysilane / graphene oxide solution were dripped on the PI surface. After spin coating for 15 seconds, it was immediately removed and placed in an 80°C oven for drying for 30 seconds. The above steps were repeated 6 times to complete the spin coating. After the spin coating was completed, the sample was placed in an oven and heated at 100°C, 150°C and 200°C for 4 hours for heat treatment to obtain a 3-aminopropyltriethoxysilane / reduced graphene oxide composite surface modified film layer.

[0055] The surface resistance of the 3-aminopropyltriethoxysilane / reduced graphene oxide coating under this mass ratio is 5.19×10 9 Ω / □After the cumulative dose is 8.01×10 20 atoms / cm 2 The mass loss after the ground atomic oxygen simulation test decreased by 98.4% compared with the original PI. After 100 hot and cold cycles at -100 to 100°C, the surface SEM morphology did not change significantly.

[0056] Example 5

[0057] Under the 5mg / mL reduced graphene oxide concentration system, a composite modified system with a mass ratio of reduced graphene oxide to organic silane of 1:3 was prepared. 7.5mg of deionized water was added to 2mL of alcohol solution containing 75mg of 3-aminopropyltriethoxysilane, and the mixture was stirred at 360rpm for 12 hours at 25°C for hydrolysis. 25mg of graphene oxide powder prepared by the Hummers method was added to 3mL of alcohol solution, and ultrasonically dispersed in an ice bath for 6 hours. After that, the graphene oxide solution was slowly added dropwise to the hydrolyzed 3-aminopropyltriethoxysilane alcohol solution, and stirred at 180rpm for 12 hours at 25°C.

[0058] Preparation and characterization of PI surface composite modified film layer. The surface activated PI substrate was cut into 2.5×3 cm rectangles and glued to the surface of the glass slide with transparent glue. The glass slide was then adsorbed on the spin coater and the rotation speed was adjusted to 1000 rpm. Different ratios of 3-aminopropyltriethoxysilane / graphene oxide solution were dripped on the PI surface. After spin coating for 15 seconds, it was immediately removed and placed in an 80°C oven for drying for 30 seconds. The above steps were repeated 6 times to complete the spin coating. After the spin coating was completed, the sample was placed in an oven and heated at 100°C, 150°C and 200°C for 4 hours for heat treatment to obtain a 3-aminopropyltriethoxysilane / reduced graphene oxide composite surface modified film layer.

[0059] The surface resistance of the 3-aminopropyltriethoxysilane / reduced graphene oxide coating under this mass ratio is 9.79×10 9 Ω / □After the cumulative dose is 8.01×10 20 atoms / cm 2 The mass loss after the ground atomic oxygen simulation test decreased by 99.0% compared with the original PI.

[0060] Comparative Example 1

[0061] The difference between this comparative example 1 and Example 3 is that: under the 4 mg / mL reduced graphene oxide concentration system, a composite modified system with a mass ratio of reduced graphene oxide to organic silane of 1:0 is prepared. The mass loss of the modified film layer of this system is only reduced by 1.10% compared with the original PI, and the anti-atomic oxygen performance is not good. The modified film layer of this system is tested for adhesion and bonding using 3M tape. The surface pure reduced graphene oxide modified film layer has obvious signs of falling off, and the bonding is poor.

[0062] Comparative Example 2

[0063] The difference between this comparative example 3 and example 3 is that only organic silane is used to prepare the modified film layer. The surface impedance of the modified film layer of this system is 4.50×10 11Ω / □, the surface conductivity is poor, and does not meet the surface anti-static standards set by NASA. If the preparation environment and other conditions are not well controlled, cracking will occur.

[0064] Comparative Example 3

[0065] The difference between this comparative example 3 and example 3 is that the organosilane used in the modification system is ethyl orthosilicate. During the preparation of the modification system, the graphene oxide is unevenly dispersed in the modification solution, and the surface of the film layer is not smooth enough and has cracks.

[0066] Table 1 shows the composition and performance parameters of the anti-oxygen / antistatic organosilane / reduced graphene oxide composite surface modified film:

[0067]

[0068] The mass ratio change and the overall concentration change can refer to the above 5 embodiments. At the same concentration, as the silane ratio increases, the atomic oxygen protection performance increases and the antistatic performance decreases. Under the same mass ratio of graphene and organosilane, as the overall concentration increases, the atomic oxygen protection performance increases.

[0069] Finally, it is necessary to explain here that the above embodiments are only used to further illustrate the technical solution of the present invention in detail and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above content of the present invention all fall within the scope of protection of the present invention.

Claims

1. A method for preparing an anti-oxygen / antistatic organosilane / reduced graphene oxide composite surface modified film, characterized in that: The anti-oxygen / antistatic organosilane / reduced graphene oxide composite surface modified film comprises: a polymer matrix, and a mixed layer of organosilane and reduced graphene oxide formed on the surface of the polymer matrix; wherein the organosilane simultaneously undergoes bonding reaction with the polymer matrix and the reduced graphene oxide; The preparation method comprises: (1) hydrolyzing aminoalkylsilane to obtain a hydrolyzed silane coupling agent containing silanol groups and amino groups; (2) mixing the graphene oxide solution and the hydrolyzed silane coupling agent containing silanol groups and amino groups to obtain a mixed solution; (3) coating the mixed solution on the surface of the polymer substrate and subjecting it to heat treatment to obtain an anti-oxygen / antistatic organosilane / reduced graphene oxide composite surface modified film; The polymer matrix is ​​a polyimide film, a polyester film or a composite film of the two; Before coating, the polymer substrate is subjected to acid-base activation treatment to form carboxyl groups on its surface.

2. The preparation method according to claim 1, characterized in that: The aminohydrocarbon silane is at least one selected from 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, aminopropylmethyldiethoxysilane and N-aminoethyl-3-aminopropyltriethoxysilane.

3. The preparation method according to claim 1, characterized in that: In the mixed layer of organic silane and reduced graphene oxide, the mass ratio of reduced graphene oxide to organic silane is 1:(1-5).

4. The preparation method according to claim 1, characterized in that: The thickness of the mixed layer of organic silane and reduced graphene oxide is 50nm-10μm.

5. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment is 100 to 200° C., and the time of the heat treatment is 1 to 48 hours.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the graphene oxide to aminosilane is 1:(1-5).

7. The preparation method according to claim 1, characterized in that: The solution used for the acid-base activation treatment includes a NaOH solution with a concentration of 0.5 to 5 mol / mL and an acetic acid solution with a concentration of 0.5 to 5 mol / mL.

8. The preparation method according to claim 1, characterized in that: The coating method is spin coating or spray coating; the spin coating speed is 500-3000 rpm, and the spin coating time is 1-60 seconds.

Citation Information

Patent Citations

  • Graphene composite material and preparation method thereof

    CN102153877A

  • Preparation method of wear-resistant coating for modifying thermosetting polyimide by using nano silicon carbide loaded reduced graphene oxide compound

    CN112852287A